2023
DOI: 10.1111/ejn.16044
|View full text |Cite
|
Sign up to set email alerts
|

Molecular changes in hippocampal energy metabolism in mice selectively bred for extremes in stress reactivity: Relevance of mitochondrial dysfunction for affective disorders

Virginie Rappeneau,
Prasanna Koti,
Lars Wilmes
et al.

Abstract: Affective disorders, such as major depression, are frequently associated with metabolic disturbances involving mitochondria. Although dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis is known to alter energy metabolism, the precise mechanisms linking stress and metabolic disturbances are not sufficiently understood. We used a mouse model of affective disorders to investigate the impact of a genetic predisposition for extremes in stress reactivity on behavioural and metabolic phenotypes as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 112 publications
0
1
0
Order By: Relevance
“…1-Monopalmitin is a lipid responsible for amongst others, storing energy and acting as a structural component of cell membranes (Qin et al, 2021). Consequently, that MSEW induced a reduction in hippocampal 1-monopalmitin of FSL rats (Table 3) could suggest a negative effect on mitochondrial function and is strongly supported by the robust preoteomics analysis of Mallei et al (2015) on the Flinders strain and recent findings linking stress-related pathways, stress reactivity and the effects on mitochondrial function (Rappeneau et al, 2023). Nevertheless, it is worth noting that despite their not being any statistical strain differences in hippocampal 1-monopalmitin levels, O' Gorman et al (2017) reported plasma 1-monopalmitin levels to be reduced in children and adolescents suffering from psychotic disorders.…”
Section: The Effect Of An Early-life Stressor On Bio-behavioural Para...mentioning
confidence: 75%
“…1-Monopalmitin is a lipid responsible for amongst others, storing energy and acting as a structural component of cell membranes (Qin et al, 2021). Consequently, that MSEW induced a reduction in hippocampal 1-monopalmitin of FSL rats (Table 3) could suggest a negative effect on mitochondrial function and is strongly supported by the robust preoteomics analysis of Mallei et al (2015) on the Flinders strain and recent findings linking stress-related pathways, stress reactivity and the effects on mitochondrial function (Rappeneau et al, 2023). Nevertheless, it is worth noting that despite their not being any statistical strain differences in hippocampal 1-monopalmitin levels, O' Gorman et al (2017) reported plasma 1-monopalmitin levels to be reduced in children and adolescents suffering from psychotic disorders.…”
Section: The Effect Of An Early-life Stressor On Bio-behavioural Para...mentioning
confidence: 75%